Systematic study of neutron emission model for nuclear muon capture experiment - Othman, Faiznur (2017)
Neutron emission model is important for muon capture experimental verification. It provides giant resonance estimation for neutron nuclear response by muon charge exchange reaction. This study uses the neutron emission model for muon capture experiment developed in 2014 and investigate the relationship of three parameters involve in neutron emission namely percentage of the pre-equilibrium event(x), excitation energy (Eiex), and the nuclear temperature factor (y). The influence of these parameters to the neutron energy spectrum are observed. The results are compared with the previous study on neutron emission spectrum of 16O, 32S, 40Ca, 207Pb and 209Bi from muon capture experiment. The relationship between x, Eiex and y are deduced. The outcome of this study may provide consistency guide for neutron emission after muon capture experiment. The result can be deduced as x = 0.41 A 0.48, Eiex = 17.31 A 0.0020 and y = 8.76 A 0.20.